A Benzimidazole-Based Fluorescent Probe for the Selective Recognition of Cobalt (II) Ions - Jing Zhu; Hua-Fen Wang; Jia-Xiang Zhang; Man Wang; Yu-Wei Zhuang; Zhi-Guang Suo; Ye-Wu He; Yan-Chang Zhang; Min Wei; Hai-Yan Zhang (Molecules)
Cobalt, a rare element in the Earth’s crust, is widely used in industries due to its hardness and antioxidant properties. It also plays a vital role in physiological functions, being a key component of vitamin B12. However, excessive cobalt intake can cause health issues. Detecting cobalt ions, especially Co2+, in food is crucial due to potential contamination from various sources. Fluorescent probes offer high sensitivity, selectivity, a rapid response, and ease of use, making them ideal for the accurate and efficient recognition of Co2+ in complex samples. In this context, a highly selective fluorescent probe, 2,2′-((3-(1H-benzo[d]imidazol-2-yl)-1,2-phenylene) bis(oxy)) bis(N-(quinolin-8-yl) acetamide) (DQBM-B), was synthesized using chloroacetyl chloride, 8-aminoquinoline, 2,3-dihydroxybenzaldehyde, and benzidine as raw materials for the recognition of Co2+. Probe DQBM-B can exhibit fluorescence alone in DMF. However, as the concentration of Co2+ increased, Photoinduced Electron Transfer (PET) occurred, which quenched the original fluorescence of the probe. Probe DQBM-B shows better selectivity for Co2+ than other ions with high sensitivity (detection limit: 3.56 μmol L−1), and the reaction reaches equilibrium within 30 min.